Photoelectrochemical CO2 reduction using a Ru(ii)–Re(i) multinuclear metal complex on a p-type semiconducting NiO electrode1. Issue 53 (7th July 2015) - Sahara, Go; Abe, Ryu; Higashi, Masanobu; Morikawa, Takeshi; Maeda, Kazuhiko; Ueda, Yutaro; Ishitani, Osamu
<x xml:space="preserve">Abstract</x> A photocathode for CO2 reduction was developed using a hybrid comprising a Ru(ii)–Re(i) supramolecular photocatalyst and a NiO electrode. Photoexcitation of the Ru photosensitizer selectively gave CO with high faradaic efficiency.